Republic of Lebanon : Hydrocarbon Strategy Study - World Bank (Washington, DC, 2013)
The power sector in Lebanon is dominated by the national electric utility, Electricite du Liban (EdL), which is organized under the Ministry of Energy and Water (MEW). EdL's assets, human resources, and administrative facilities were severely damaged during the period of civil war in Lebanon, and most efforts in the post-war period have been on the rehabilitation of assets, with a lesser focus on strengthening the company from an institutional, administrative, and financial perspective. As a result, the company is characterized by lack of technical and managerial capacity, lack of systems to manage and monitor performance, and a weak financial situation, with close to US$400 million in deficit every year and a quickly deteriorating balance sheet (retained losses now exceed US$1 billion). At the operational level, losses, primarily nontechnical, are approaching 50 percent and continued transmission constraints and unreliable service have resulted in a surge in self-generation. Attempts to privatize EdL have failed because of the lack of financial performance required to attract investors. The government is very concerned about the fiscal drain EdL poses and is seeking options to improve the company's, and the sector's, performance. As an immediate priority, the Government of Lebanon should (a) put measures in place to improve the financial and operational performance of EdL (through, inter alia, the introduction of an interim Management Contract); and (b) in parallel, develop a long-term strategy for reforming and restructuring the sector with a view of increased level of private sector participation in the financing and operation of the sector and efficient competition.